Stellar Halos: modelling formation in the L-Galaxies 2020 semi-analytic model - Murphy, Geoff (Department of Astronomy, 2021)
A study was carried out to determine how well the L-Galaxies 2020 semi-analytic model simulates the stellar halos of galaxies and the intracluster stellar (ICS) components of galaxy clusters. Two galaxy disruption models were tested, namely instantaneous disruption and gradual disruption. Furthermore, two stellar halo profiles were applied to the simulation results: a power-law profile with slope γ = −3.5 and a Navarro-Frenk-White (NFW) profile. In the latter case, the stellar halo stars follow the distribution of the galaxy's dark matter. It was found that a combination of an NFW profile and gradual disruption provided the best results across the widest range of literature data, namely measurements of stellar halo mass, total stellar mass, stellar mass fractions, and stellar halo iron abundances. Gradual disruption of satellite galaxies also resulted in the central galaxies having more massive stellar halos in comparison to instantaneous disruption. Additional stellar halo formation mechanisms, such as in-situ star formation, were not needed, as the stellar halo masses seen in observations can be obtained in L-Galaxies by considering only tidal disruption of infalling satellite galaxies. The number of high mass accretions into the halos of Milky Way-mass galaxies in the gradual disruption model agreed well with simulation literature. It was found that while central galaxies can induce many disruptions of satellite galaxies (over a thousand in some cases), the majority of the Milky Way-sized stellar halos in L-Galaxies are formed by the disruption of one to fourteen satellite galaxies, in good agreement with simulation literature. A population of galaxies with unexpectedly low stellar halo iron abundances was found. These were determined to be a result of disruptions of high mass, low metallicity satellite galaxies. Furthermore, rather than iron or oxygen, carbon was found to be the dominant element produced by stellar halo stars for the majority of redshifts in most high mass central and satellite galaxies, due mainly to asymptotic giant branch stars. The relative contribution of stellar halo stars was found to be minor, however, with circumgalactic medium enrichment from halo stars in comparison to outflows from galactic stars being on average . 1%. For clusters with virial masses exceeding 1.6 × 1014M, the brightest central galaxy and ICS (BCG+ICS) stars contained 42.44% of the total cluster stellar iron content, while the fraction MICS MBCG+MICS was found to be 82.50%, both results being in good agreement with observation.